Medicinal forage and herbal diets: a new approach to sustainable farming - Zehtab Salmasi, Saeid (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Medicinal and aromatic plants have long been used in traditional medicine, for preparing food or feeding livestock as well as during religious ceremonies and to manufacture cosmetics. The concept of “medicinal forage” refers to plants that provide both nutrition and medicinal benefits to animals, forage crops containing active compounds or secondary metabolites, as well as the method of intercropping medicinal plants with forage crops. Aromatic plants, herbs and their derivatives such as essential oils have been studied in the literature for their potential application to replace antibiotics in ruminant diets. In the research world, scientists are examining natural plant compounds like tannins, saponins and essential oils which could become part of alternative applications for antibiotics. Herbal diets can reduce, and sometimes negate the disease incidence in animals; increase reproductive health of livestock and sustainable weight gain. The economic benefits are typically decreased veterinary expenses, higher profits because of a lower cost to production ratio and the premium consumers will pay for organic products. The inclusion of medicinal forage and herbs in the diet can be used as a tool to increase animal welfare and productivity but also brings agriculture towards sustainability through animals raised organically by associating different species.